Study on measurement reliability based on Liu estimator. (31st May 2018) - Huang, Jiewu; Ma, Lie; Li, Rong
Summary: In this paper, we introduce the Liu estimator in the measurement process as an alternative method to the ordinary least squares estimator. To compare the Liu estimator and the ordinary least squares estimator under the reliability criterion, a simulation study is conducted. Simulation study results show that the Liu estimator is an effective method to replace OLS estimator in process measurement. When the Liu parameter is chosen from a reasonable range, the Liu estimator is superior to the ordinary least squares estimator in terms of reliability.